2016
DOI: 10.1051/e3sconf/20160903004
|View full text |Cite
|
Sign up to set email alerts
|

Inputs from in situ experiments to the understanding of the unsaturated behaviour of Callovo-Oxfordian claystone

Abstract: Abstract. The French national radioactive waste management agency (Andra) research program is dedicated to preparing the construction and operation of a deep geological disposal facility for high-level and intermediate-level long-lived radioactive waste (HL, IL-LLW) in the Callovo-Oxfordian claystone (COx). The characterization of the COx thermo-hydro-mechanical (THM) behavior, at different scales of interest, must gradually give relevant data for design and safety calculations. The effects of saturation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the present analysis, however, the simulation of the unsaturated zone in the COx claystone is not a major objective and, therefore, the zero liquid pressure boundary condition is considered appropriate. In addition, ventilation experiments at the Mont Terri (Mayor et al, 2007) and MHM (Armand et al, 2016) URLs revealed that the effect of dry air circulation is very limited, and the unsaturated zone extends only a very short length into the claystone.…”
Section: Main Features Of the Finite Element Modelmentioning
confidence: 99%
“…In the present analysis, however, the simulation of the unsaturated zone in the COx claystone is not a major objective and, therefore, the zero liquid pressure boundary condition is considered appropriate. In addition, ventilation experiments at the Mont Terri (Mayor et al, 2007) and MHM (Armand et al, 2016) URLs revealed that the effect of dry air circulation is very limited, and the unsaturated zone extends only a very short length into the claystone.…”
Section: Main Features Of the Finite Element Modelmentioning
confidence: 99%
“…Under natural conditions, potential clay host rocks as well as active clay liners or clay backfills are generally water saturated. During the construction of an underground repository, however, the contact with the unsaturated atmosphere leads to a partial desaturation of the rocks (e.g., Gimmi et al, 1997;Armand et al, 2016). Also, the bentonite backfill will be emplaced in a dry state, which may lead to a partial desaturation of the surrounding rock (e.g., Gens et al, 2002;Dessirier et al, 2016).…”
Section: Influence Of Partial Saturationmentioning
confidence: 99%
“…Armand et al [3] reported that the convergence of the drifts was affected by the pattern and the density of fractures in EDZ. Moreover, unsaturation in COx claystone was also induced by the ventilation in URL [4]. In this case, it is important to well understand the hydro-mechanical behaviour of damaged COx claystone for estimating the safety performance of potential repository.…”
Section: Introductionmentioning
confidence: 99%